First principles calculations of the structural, electronic, magnetic, and thermodynamic properties of the Nd2MgGe2 and Gd2MgGe2 intermetallic compounds - S. Menouer (Nature Portfolio, 2021)
Abstract In recent years the intermetallic ternary RE2MgGe2 (RE = rare earth) compounds attract interest in a variety of technological areas. We therefore investigate in the present work the structural, electronic, magnetic, and thermodynamic properties of Nd2MgGe2 and Gd2MgGe2. Spin–orbit coupling is found to play an essential role in realizing the antiferromagnetic ground state observed in experiments. Both materials show metallicity and application of a Debye-Slater model demonstrates low thermal conductivity and little effects of the RE atom on the thermodynamic behavior.